Shear bond strength of different surface treatments in bulk fill, microhybrid, and nanoparticle repair resins - de Jesus Tavarez RR; Almeida Júnior LJS; Guará TCG; Ribeiro IS; Maia Filho EM; Firoozmand LM (Dove Medical Press, 2017)
Rudys Rodolfo de Jesus Tavarez,1 Lauber Jose dos Santos Almeida Júnior,2 Tayanne Christine Gomes Guará,1 Izabella Santos Ribeiro,1 Etevaldo Matos Maia Filho,1 Leily Macedo Firoozmand2 1Department of Restorative Dentistry, Ceuma University (CEUMA), 2Department of Dentistry I, University Federal of Maranhão (UFMA), São Luís, Maranhão, Brazil Objectives: The purpose of this study was to evaluate the influence of surface treatment and different types of composite resin on the microshear bond strength of repairs. Materials and methods: Seventy-two specimens (n=72) were prepared using a nanoparticle resin and stored in artificial saliva at 37 ± 1°C for 24 h. After this period, the specimens (n=24) were restored with microhybrid resin P60 (3M ESPE), nanoparticle resin Filtek Z350 (3M ESPE), and Bulk Fill Surefil SDR Flow (Dentsply) composite resins. Previously, the surfaces of the samples were treated, forming the following subgroups (n=12): (A) conditioned with 37% phosphoric acid for 30 s, and (B) abrasioned with a diamond tip for 3 s and conditioned with 37% phosphoric acid. In all groups, before insertion of the composite resin, the adhesive system Adper Single Bond 2 was actively applied and photopolymerized for 20 s. Results: The microshear test was executed to assess bond strength. Kruskal–Wallis (p<0.05) and Mann–Whitney statistical tests showed significant statistical difference considering that the bulk-fill resin turned out to have a lower bond strength than the conventional nanoparticle and microhybrid composites. With regard to the technique, the roughening with diamond bur followed by the application of phosphoric acid exhibited values higher than the exclusive use of acid. Conclusion: The microshear bond strength of the composite resin repairs varies in accordance with the type of composite resin utilized, and roughening the surface increased the bond strength of these materials. Keywords: bulk-fill resins, composite resins, dental restoration repair, microshear strength, surface treatment composite repair